Contrast and Contrast Variation in Neutron, X-ray, and Light Scattering - Schurtenberger, Peter ; 0000-0002-2790-8831; Oberdisse, Julian (Neutrons, X-rays, and Light : Scattering Methods Applied to Soft Condensed Matter, Second Edition, 2024)
The concept of scattering contrast is central to (small-angle) scattering of neutrons, X-rays, and visible light, as it defines the visibility to the radiation of the nano- and mesostructures under scrutiny, in their respective solvent or matrix. In this chapter, we start with the scattering process by elementary scatterers, such as nuclei or atoms, which produce secondary, scattered waves, and the amplitude of which is given by the scattering length of each scatterer. This allows us to define scattering length densities, and thus the contrast of each object, molecule, or particle with respect to the matrix for each radiation. For neutrons, we discuss the use of selective deuteration and the subtleties of coherent and incoherent scattering, as well as anomalous scattering for X-rays. The importance of a detailed understanding of the contrast, and how it gives rise to the scattered intensity, is then illustrated by the absolute determination of molecular masses, and how the contrast can be adjusted to observe only desired parts of the samples, opening the road to contrast variation experiments. In the final section, we present selected examples from polymers and chain flexibility – including zero-average contrast experiments in nanocomposites – from biological and self-assembled systems, with optical and SANS studies of microemulsions.
Keywords: Contrast variation; Matching; Scattering length; Scattering length density; Zero-average contrast